Maize susceptibility to drought at flowering: a new approach to overcome the problem - Sangoi,Luís (1998)
Among the agronomically important grasses, maize is the most susceptible to drought at flowering. Drought stimulates a protandrous pattern of development, increasing the anthesis-silking interval. Because maize has a short period of flowering and pollen remains viable for only a short period of time, each day of delay between pollen shed and silk emergence will reduce the rate of sexual fertilization and increase barrenness. The purpose of this article is to present an ideotype of maize designed to overcome this problem. The biological model described here can reduce sensitivity to water deficiency through morphological and anatomical modifications, such as the transference of the ear from the axil of a leaf to the apex of the plant; condensation of the upper stem internodes; and a reduction of plant height and leaf number. Genetic diversity was found for all traits of interest. It was possible to identify and select mutants that exhibited the proposed alterations in a single phenotype. However, associated with those mutants there were several undesirable characteristics, such as lack of vigor and disease susceptibility. To gain an agronomically acceptable phenotype with adaptation to a hot and dry environment further improvement is needed.